A Large-Insert Porcine Library with Sevenfold Genome Coverage: a Tool for Positional Cloning of Candidate Genes for Major Quantitative Traits - Jeon, J.T. (Gyeongsang national University, Jinju, Republic of Korea); Jeon, H.J (Genomics Division, Bioneer Corporation, Daejeon, Republic of Korea); Kim, T.H; Lee, K.T; Cheong, I.C; Park, Y.W. (Rural Development Adiministration, Suwon, Republic of Korea) (Molecules and cells, 2003)
A porcine genomic bacterial artificial chromosome (BAC) library was constructed by cloning partial EcoRI-digested high-molecular-weight DNA from a Korean native boar into the EcoRI site of the pBACe3.6 vector. The library consists of about 165,000 clones with an average insert size of 125 kb, representing about seven genome equivalents of coverage.